FUNGSI SUBJEK DALAM PIDATO SAN BERNARDINO TERROR ATTACK AND THE WAR ON ISIS OLEH BARACK OBAMA ( SEBUAH ANALISIS SINTAKSIS) - WAGUNU, OSINNIAWATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled ? The Function of Subject Used in the Speech San Bernardino Terror  Attack  and the War on ISIS by Barack Obama?. The objectives of  this research are to identify and classify the types of  functions subject and to analyze the realizations of  functions subject. This  research  uses  a  descriptive method. There are three steps to finish this research.  First step is preparation, the writer  reads the speech to find out the data. Second step is data collection. The writer collects the subject found in the speech  and  compares  them with the speech text then the writer identifies and classifies the kinds of  function subject  according to the theory of  Aarts and Aarts (1982).  Third step is data analysis, to analyze  the  data  about  the  realizations of  functions subject, the writer uses the theory from Aarts and Aarts (1982) to analyze  and  describe  the realizations of function subejct. The  result of  this  research:  First,  it  shows  that according to the theory of Aarts and Aarts (1982), there are four criteria of  functions subject, but there were only three criteria of  function  subject  found  in this speech, those are Position, Concord,  Passivization.  Furthermore, the   six realizations  of  function subject, those are  Noun Phrase,  Finite Clause, Non- Finite Clause, Anticipatory it + Finite/Non-Finite  Clause, Unstressed  there in existential    sentences, and Prepositional Phrase found  in the speech  San Bernardino Terror  Attack  and the War On ISIS.  The   findings of  this  research support  the  theory  of  Aarts and Aarts (1982).   Keywords: Function Subject; Obama?s Speech, Syntax; Aarts and Aarts